Local Wisdom of Lubuk Larangan in Subayang River as a Source of Learning Environmental Education - Wulandari, Sri; Suwondo, Suwondo; Haryanto, Rudy (Proceedings of the UR International Conference on Educational Sciences, 2018)
Riau Province has a diversity of local wisdom, including the local wisdom of Lubuk Larangan in Subayang River. This research was conducted to find out whether the local wisdom of lubuk larangan in Subayang River can be integrated as a learning resource environmental education for students. The study was conducted in Batu Songgan, Muarobio and Tanjung Belit Villages, Kampar Kiri Hulu Subdistrict, Kampar District, Riau Province in August-September 2018. Data collected are the local wisdom of lubuk larangan and environmental education curriculum through interviews, field observations, and documentation. Data analysis was a descriptive qualitative way to identify the potential for integrating local wisdom as a learning resource. The study results show that the people of Batu Songgan, Muarobio, and Tanjung Belit Villages have are local wisdom values in environmental management efforts. The Environmental Education Course has Sub-Learning Outcomes